Communicating Italy to British and American tourists between the wars: tourist representations of Italy and adaptation to the specificity of the target audience (Altre Modernità, 2025)
The study of tourism discourse in the first decades of the twentieth century is important for its central role in the formation of individual and collective identities. This period witnessed a remarkable transition in which tourist discourse functioned not only as a means of communication, but also as a stage for the expression of different identities. Such articulation within the discourse laid the groundwork for the development of contemporary tourism practices. However, a crucial area that needs to be explored is the role of tourism promotion, particularly in relation to institutional tourism communication in foreign languages during the inter-war period. It is worth investigating the extent to which promoters in the early 1920s understood the objectives and methods required to shape the image of a destination. This study examines the strategies used to promote Italy to English-speaking tourists during the early stages of institutional tourism promotion, marked by the creation of ENIT in 1919. In particular, it analyses the evolution of approaches aimed at increasing the effectiveness of tourism promotion and targeting.
Keywords: Tourism promotional discourse; tourism studies; tourism translation; tourism history; translation and adaptation